Analysis of public perception about the performance of village government apparatus in Public Service - Lingga Wisma Angga Saputro; Daryono Daryono; Adi Nur Aziz (Journal of Innovative and Creativity, 2025)
Public service is one of the main duties of village government apparatus in meeting the needs of the community. This research is motivated by the importance of the role of village apparatus in realizing fair, prompt, and equitable service. The aim of this study is to determine the community's perception of the performance of the Watuprapat Village government apparatus in delivering public services, as well as to identify the factors influencing their performance and the efforts made to improve it. This research is based on the theoretical review of public apparatus performance, community perception, and public service concepts. The approach used is qualitative descriptive, with data collected through in-depth interviews with community informants and village officials. Data analysis was carried out thematically, referring to the research focus. The results of the study show that most of the community considers the performance of the village apparatus to be quite good, particularly in administrative services and communication. However, there are still some obstacles such as lack of time discipline, limited facilities, and technical challenges in the service system. The conclusion of this research is that community perceptions of village apparatus performance tend to be positive, although some weaknesses still need to be addressed. Factors affecting performance include apparatus competence, community participation, facility conditions, and existing regulations. The village government has made various efforts such as training, the formation of integrated service teams, and community involvement to improve the quality of future services.